Gastrointestinal stromal tumors - A. P. Seryakov (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
The aim of review. To present up-to-date data on diagnostics of gastrointestinal stromal tumors (GIST) and experience N.N. Burdenko Chief military clinical hospital in treatment of such patients.Original positions. Gastrointestinal stromal tumors, that were described in 1983 by M.T.Mazur and H.B.Clark, fall into to group of rare tumors of gastro-intestinal tract of mesenchymal origin with characteristic morphological and immunohistochemical pattern. Issues of treatment of these patients were extremely actual. Surgical resection was the first line treatment, however the mean survival rate after successful operative treatment was only 5 years, even at complete resection. In the case if relapse or metastases occurs surgical methods were ineffective, and chemo- or radiation therapy allowed to receive rather limited response (in particular, survival rate at late stages of GIST did not exceed 1 year). Diagnostics, treatment and outcome at patients with GIST underwent significant changes for last 10 years due to discovering of molecular mechanisms, resulting in development of tumor: activated mutations of KITand PDGFR α-tyrosine kinase. These findings promoted development of tyrosine kinase inhibitor – imatinib which demonstrated essential advantage in terms of survival rate of patients. Experience of treatment GIST within N.N. Burdenko Chief military clinical hospital corresponds the level of leading clinics.Conclusion. Discoveries in the area of GIST biology allowed to introduce the new scientific and practical developments in treatment of patients.